Solid lipid nanoparticles: Preparation techniques, their characterization, and an update on recent studies - Koduru Trideva Sastri, Gadela Venkata Radha, Sruthi Pidikiti, Priya Vajjhala (Journal of Applied Pharmaceutical Science, 2020)
Solid lipid nanoparticles (SLNs) have emerged as a remarkable nanocolloidal system for drug delivery. This review presents contemporary information regarding various aspects about SLNs, i.e., SLN morphology, structural features, preparatory methods, and their characterizations. This carrier system allows advancing the therapeutic efficacy of drugs belonging to several categories. The present uses of SLNs include cancer therapy, infectious conditions, diabetes, central nervous system disorders, cardiovascular disorders, cosmeceuticals, and others. SLNs facilitate improved the pharmacokinetics and modify the drug releases. The prospect of surface modification, enhanced permeation against various biological barriers, the ability to resist chemical degradation, and the possibility of encapsulation of two or more therapeutic agents simultaneously has gained attention for SLNs universally. Simultaneously, this review emphasizes on recent research trends pertaining to this carrier system.
Keywords: Solid lipid nanoparticles, carrier system, nanomedicine, biocompatibility, nanotechnology.